Phenomenological Study of Survivors During The Covid-19 Illness - Srimiyati Srimiyati; Ketut Suryani; Agnes Agnes; Prisca Ika Pratiwi (Sekolah Tinggi Ilmu Kesehatan (STIKes) Karya Husada Semarang, 2022)
Covid-19 is a very dangerous virus that attacks a person's respiratory system. This virus infects many people in the world. The process of transmission is by splashing the saliva of an infected person. Various phenomena are obtained from people infected with the Covid 19 virus, such as emotional disturbances, physical disorders, and psychological disorders. The aim is to dig deeper through the phenomenological study of survivors during the Covid-19 illness. This qualitative research uses a phenomenological approach. Purposive sampling technique for taking participants with the criteria of being diagnosed with Covid-19 for more than 5 days, undergoing isolation, being able and willing to share their experiences, willing to become participants. Data collection was carried out by in-depth interviews using interview guidelines, recorded with a tape recorder. The number of participants was 5 participants. Data analysis using Colaizzi analysis. The results of the study obtained four themes 1) Initial feelings when testing positive for Covid-19, 2) Body disturbances felt when infected with Covid 19, 3) Responses and reactions during independent isolation, and 4) support and motivation obtained while experiencing Covid-19. Suggestions for someone who is sick with Covid 19 needs a positive coping in undergoing isolation. Support and support from the environment, both family and friends, and compliance more with health protocolsKeywords: covid 19; experience; participantStudi Fenomenologi Penyintas Selama Sakit Covid-19ABSTRAK Covid-19 merupakan suatu virus sangat berbahaya yang menyerang sistem pernafasan seseorang. Virus ini banyak menginfeksi manusia di dunia. Proses penularan dengan percikan air ludah dari orang yang terinfeksi. Berbagai fenoma yang didapatkan dari orang yang terinfeksi virus covid 19 seperti gangguan emosional, gangguan fisik, gangguan psikologi. Tujuannya untuk menggali lebih dalam melalui studi fenomenologi Penyintas selama sakit Covid-19. Penelitian ini kualitatif menggunakan pendekatan fenomenologi. Teknik pengambilan partisipan purposive sampling dengan kriteria terdiagnosa covid-19 lebih 5 hari, menjalani isolasi, mampu dan mau mengungkapkan pengalamannya, bersedia menjadi partisipan. Pengambilan data dilakukan wawancara mendalam menggunakan pedoman wawancara, direkam dengan alat rekam. Jumlah partisipan 5 partisipan. Analisa data menggunakan analisa Colaizzi. Hasil penelitian didapatkan empat tema 1)Perasaan awal saat dinyatakan positif Covid-19, 2) Gangguan tubuh yang dirasakan saat terinfeksi Covid 19, 3)Respon dan reaksi selama isolasi mandiri, 4) suport dan motivasi yang didapatkan selama mengalami covid-19. Saran sesorang yang mengalami sakit covid 19 diperlukan suatu koping yang positif dalam menjalani isolasi. Support dan dukungan dari lingkungan baik keluarga maupun teman, dan lebih mentaati protocol kesehatan.Kata Kunci: covid 19; pengalaman; partisipan